2004
DOI: 10.1002/sim.1775
|View full text |Cite
|
Sign up to set email alerts
|

Repeated-measures models with constrained parameters for incomplete data in tumour xenograft experiments

Abstract: In cancer drug development, xenograft experiments (models) where mice are grafted with human cancer cells are used to elucidate the mechanism of action and/or to assess efficacy of a promising compound. Demonstrated activity in this model is an important step to bring a promising compound to humans. A key outcome variable in these experiments is tumour volumes measured over a period of time, while mice are treated with an anticancer agent following certain schedules. However, a mouse may die during the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 26 publications
0
48
0
Order By: Relevance
“…The results showed that irinotecan was highly active whereas temozolomide had little activity in the Rh18 xenograft. The data analysis showed some evidence for synergism but it fell short of statistical significance (39).…”
Section: Dose Schedule and Combination Regimensmentioning
confidence: 84%
See 2 more Smart Citations
“…The results showed that irinotecan was highly active whereas temozolomide had little activity in the Rh18 xenograft. The data analysis showed some evidence for synergism but it fell short of statistical significance (39).…”
Section: Dose Schedule and Combination Regimensmentioning
confidence: 84%
“…Response surface modeling provides an effective statistical approach to modeling complex patterns of synergy, additivity, and antagonism in the same data set (39,88). Tan et al (39) developed a class of repeated-measures models to analyze the dose-response relationship in xenograft experiments while accounting for incomplete (missing at random and informative censoring) and variable constraints.…”
Section: Dose Schedule and Combination Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all tumor systems are useful for study, with for example, the occurrence of ''no takes, '' rendering the statistical definition of activity problematic (6). Guidance and advice from a biostatistical consultant is key and plays to the value of mouse xenografts in contrast to transgenic systems in that appropriately staged tumors can be reliably and economically generated to allow evaluation of a series of compounds (19). Second, as we evolve toward the more routine evaluation of targeted therapeutics, for a new molecular entity whose target is defined, understanding the in vitro area under the pharmacologic plasma concentration-time curve producing the desired target effect is an essential piece of information that is not as frequently addressed as it should.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, mixed-effects models have become a convenient approach to model various experimental factors, such as treatment effects or base levels (fixed effects) while accounting for variation expressed by individual animals or tumors (random effects). This model family has successfully been used to analyze specific types of xenograft experiments or study questions (12)(13)(14)(15)(16)(17). However, further challenges remain.…”
Section: Introductionmentioning
confidence: 99%